THE INFLUENCE OF PRODUCT VARIETY AND CUSTOMER EXPERIENCE ON CUSTOMER SATISFACTION - Sri Lestari; Leonard Adrie Manafe (International Journal of Economics, Business and Accounting Research (IJEBAR), 2023)
The abundance of traders who sell various kinds of light snacks at very affordable prices, makes competition in the world of trade more intense thus sales increase more rapidly. For this reason, basreng ("Kedai77") products are produced as light snacks for the millennial generation that are able to compete with other light snack products that can attract customers' desire to buy and increase the number of purchases. This research was tested using quantitative methods by distributing questionnaires as a way for data to be collected. Then the data that has been collected can be analyzed with the help of SPSS Version 21 tools. The 100 respondents involved in the research included 61 women and 39 men. The age range is 12-65 years. The results of the study concluded that the variables of product variety and customer experience simultaneously affect Kedai77 customer satisfaction. From the partial determination coefficient, it is stated that the customer experience variable is more dominant than the product variation variable that affects customer satisfaction in purchasing basreng.